Proceso de cuidado de Enfermeria en infante con Sindrome Obstructivo Bronquial (SOB) neumonia hospitalizado en emergencia de un hospital de Lima ,2021 - Suarez-Acuña, Luzgart-Jacqueline (2022)
The present work develops the nursing care process (NCP) to a pediatric patient, with the aim of identifying problems and managing comprehensive care for infants with a diagnosis of broncho-obstructive syndrome (BOS)-Pneumonia hospitalized in the emergency area. Single case study, qualitative approach, NCP method. The data collection was carried out through the observation technique, physical examination and as an instrument the assessment framework for 11 functional patterns of Marjory Gordon, identifying 5 Nursing Diagnoses prioritizing three of them: Ineffective cleaning of the airways related to excessive mucus, evidenced by abnormal respiratory sounds crackles, wheezing, persistent cough with abundant yellowish and dense secretions in regular quantity, respiratory rate 46 breaths per minute. Impaired gas exchange associated with changes in the alveolar-capillary membrane, evidenced by dyspnea, decompensated respiratory alkalosis, abnormal arterial pH 7.50, pCO2: 33 mm Hg, hypoxemia pO2: 88 mm Hg and HR tachycardia: 126 x ', oxygen saturation 86%. Hyperthermia associated with disease secondary to BOS Pneumonia, evidenced by skin hot to the touch, tachypnea (146 x '), Temperature: 38 °C planning with taxonomy II NANDA I NOC (or Nursing Outcomes Classification) and NIC (or Nursing Interventions Classification), intervention labels were executed with programmed activities being then evaluated with NOC labels and indicators respectively. The results were +1, +1, +3. Concluding that the management of care, applying NCP in a pediatric patient with BOS-pneumonia was effective, indicates that the child did not present any complications during the shifts attended in the study.